Определение зависимости фактора кооперативностн при плавлении ДНК от ионной силы - Козявкин, С.А.; Миркин, С.М.; Амирикян, Б.Р. (Биополимеры и клетка, 1986)
Получены значения фактора кооперативности в широком диапазоне ионных сил. Показано, что при уменьшении концентрации натрия от 1 до 0,01 М величина фактора кооперативности падает на три порядка, причем при высоких ионных силах она изменяется слабее, чем при низких. Отримано значення фактора кооперативності в широкому діапазоні іонних сил. Показано, що при зменшенні концентрації натрію від 1 до 0,01 М величина фактора кооперативності падає на три порядки, причому за високих іонних сил вона змінюється слабкіше, ніж за низьких. The melting temperatures for the d(AT)₂₄·d(AT)₂₄ stretch located inside the DNA helix or terminally have been determined in a wide range of the ionic strength values (0.01–1 M Na⁺). The values of cooperativity factor were calculated from the shifts in the melting temperature of the stretch due to its different boundary conditions. With a decrease of the sodium concentration from 1 to 0.01 M the cooperativity factor has dropped by three orders of magnitude, its change being less pronounced at high ionic strengths than at low ones.